8-Hydroxyquinoline and Hydroxamic Acid Inhibitors of Botulinum Neurotoxin BoNT/A - J. Dickerson, Tobin; R. Smith, Garry; C. Pelletier, Jeffrey; B. Reitz, Allen (Current Topics in Medicinal Chemistry, 2014)
We describe here the state of the art of certain aspects concerning potential small molecule therapy directed toward botulism, by inhibition of the zinc-protease containing light chain (LC) of botulinum neurotoxin BoNT/A from the anaerobic bacillus Clostridium botulinum. Botulinum neurotoxins (BoNTs) are comprised of eight serologically-distinct proteins (A – H), several of which are further divided, such as BoNT/A which has five subtypes. The BoNTs are the most toxic substances known to mankind, causing a form of flaccid paralysis that can be rapid and is often lethal. BoNT/A is comprised of a 100 kDa heavy chain (HC) attached via a single disulfide Cys-Cys bond to a 50 kDa LC. The HC mediates transport to and uptake by presynaptic glutamatergic neurons, where the LC cleaves the protein SNAP-25 and thus prevents vesicular trafficking and release of acetylcholine. The Zn-endoprotease activity of the LC of BoNT/A is a target for the development of small molecule inhibitors of BoNT/A-mediated toxicity. A variety of BoNT/A LC inhibitors have been described to date and we focus here primarily on the Zn-binding 8-hydroxyquinoline structural type as well as some of the previously-described hydroxamic acids.
Keywords: structural biology